Handbook on demographic change and the lifecourse - Falkingham, Jane; Evandrou, Maria; Vlachantoni, Athina
Showcasing ways in which the theory of the lifecourse has been applied in demographic research, this innovative Handbook uses key datasets to offer a deeper understanding of the causes and consequences of demographic change across the lifecourse. This Handbook features contributions from leading international demographers and social scientists, covering a range of substantive areas such as employment, health, migration, social security, family formation, housing and inequality to give substance to investigations into the individual's lifecourse. Chapters highlight major theoretical and methodological advances in lifecourse research and present research that sheds light on family dynamics, health and mobility over the lifecourse, illustrating the implications of lifecourse research for policy and reform. Comprehensive and cutting-edge, this Handbook will be crucial reading for students and researchers of demography, social policy, sociology and gerontology at all levels looking to enhance their own research agendas. Policy makers and practitioners of demographic research will also benefit from its insights into the key methodological avenues for advanced investigations. --
Includes bibliographical references and index.
Keywords: Demographic transition; Life cycle, Human -- Social aspects; Population research; Life cycle, Human -- Social aspects; Demographic transition; Population research